Carbon footprint and emission reduction potential of the artwork auction market - Qian, Chenxiang; Chen, Jiahui; Sun, Chuanwang (Frontiers in Energy Research, 2023)
Greenhouse gas emissions from human activities have become the leading cause of climate problems. Reducing greenhouse gas emissions from human economic activities and realizing carbon neutralization are the main means of sustainable economic development. Among them, carbon emission reduction of large-scale activities including auctions bears the brunt. Through the emission factor method, this paper estimates the carbon footprint of a typical artwork auction and divides the auction market into different sizes, according to the average round-trip distance of the number of participants. The results show that a typical 3-day medium-sized artwork auction with 500 people’s carbon footprint is about 270 tons of carbon dioxide. The traffic carbon emission of participants accounts for a large proportion of the total carbon footprint, particularly composed of the traffic carbon emissions of a small proportion of long-distance participants. Therefore, the transition from offline to virtual artwork auctions can significantly reduce the carbon footprint by 90%–95%. We put forward suggestions on improving the auction carbon footprint accounting process and industry carbon neutralization system, and promoting the development of relevant technologies for the virtual artwork auction market.